A Collaborative Approach to Promote Sustainable Learning for Vulnerable Learners in Zimbabwean Rural Secondary Schools - Chidakwa, Nowell; Lunga, Prosper; Khanare, Fumane Portia (Educational Challenges, 2024)
Purpose. Many children who attend rural schools are faced with challenges which make them vulnerable. Vulnerability does not only affect those learners, but it also disrupts the teaching and learning process; that is teachers and other learners and the well-being of people in the community. Arguably, the responsibility of supporting learners who are vulnerable so that they can attain an education which is sustainable rests in the hands of the entire community. The purpose of this study was to explore how a collaborative approach utilising community capitals can promote sustainable learning for vulnerable learners in Zimbabwean rural secondary schools. The study used the Community Capitals Framework (CCF) as the analytical framework for the study. Methodology. The study employed a qualitative methodology using Participatory Action Research (PAR) and Critical Emancipatory Research (CER) paradigms. Data were generated through discussion meetings and photovoice with learners, teachers, and parents from two rural secondary schools in Zimbabwe. Fairclough’s (1992) critical discourse analysis principles and a photovoice methodology were used for data analysis. Results. Results show that there is a need to develop a good learning environment, community engagement, and untap opportunities in local capitals to support the vulnerable learners, enhancing sustainable learning. The study also stresses the need for a positive relationship and engagement with communities, alongside leveraging all the types of capital in the community, including human capital, cultural capital, built capital, and social capital to mitigate some of the risks that learners may face. Conclusions. From the study, it is evident that a stakeholder-supported approach and leveraging on community capital is an appropriate way of addressing learner vulnerability and fostering learning in the rural secondary schools in Zimbabwe. The involvement of the community can also be used as a force to encourage the development of an environment conducive to learning that will foster the achievement of the education goals for vulnerable learners.